Patterns of complementary feeding introduction and associated factors in a cohort of Brazilian infants - Almeida, Maiara Aparecida Mialich [UNESP]; Corrente, José Eduardo [UNESP]; Vidal, Edison Iglesias de Oliveira [UNESP]; Gomes, Caroline de Barros [UNESP]; Rinaldi, Ana Elisa Madalena; Carvalhaes, Maria Antonieta de Barros Leite [UNESP] (Springer Nature, 2024)
Background: Understanding the timing of food introduction in infants is essential for promoting optimal complementary feeding practices. However, existing studies often rely on cross-sectional data, limiting the ability to capture age-specific patterns. We aimed to describe food introduction during the first year of life by identifying patterns related to age at food introduction and associated factors in a cohort of Brazilian infants. Methods: Data were collected through standardized questionnaires administered to mothers via face-to-face interviews during the infant’s first month of life and at 3, 6, 9, and 12 months of age. Additionally, two telephone interviews were conducted at 2 and 4 months of age. Information regarding food intake was assessed using a list of 48 foods, with two key aspects recorded: whether the food was introduced (yes/no) and the age at introduction. To define food introduction patterns, we employed k-means cluster analysis. Hierarchical Poisson multiple regression was employed to examine the associations between sociodemographic, biological, and healthcare factors and patterns of food introduction. Results: Three distinct patterns were identified and named according to their main characteristics: Pattern 1 – “Low Infant Formula and Timely CF Introduction”; Pattern 2 – “High Infant Formula and Early CF Introduction”; and Pattern 3 – “High Infant Formula and Later Ultra-processed Food Introduction”. Breastfeeding at six months showed a positive association with Pattern 1 (PR = 1.40; 95% CI = 1.10–1.80), while bottle use at four months was negatively associated with Pattern 1 (PR = 0.68; 95% CI = 0.53–0.87). No variables studied exhibited an association with Pattern 2. For Pattern 3, higher prevalences were observed among children whose mothers were aged < 20 years (PR = 1.54; 95% CI = 1.13–2.01) or > 34 years (PR = 1.42; 95% CI = 1.04–1.93). Not receiving guidance on the recommended duration of breastfeeding and complementary feeding during prenatal care was associated with a higher prevalence of children in this pattern (PR = 1.35; 95% CI = 1.01–1.80). Conclusions: We identified three distinct patterns of age at food introduction in the study population, although none perfectly aligned with Brazilian or WHO dietary recommendations. These findings underscore the need for targeted interventions to promote timely and healthy complementary feeding practices in Brazilian infants.
Keywords: Child nutrition; Cluster analysis; Complementary feeding; Dietary patterns